High-transparency adhesion nanocellulose-based antibacterial hydrogel as well as preparation and application thereof
By using nanocellulose, guanidine-based antibacterial agent and other components for physical-chemical crosslinking in medical hydrogels, a highly transparent adhesion nanocellulose-based antibacterial hydrogel was developed, which solved the problem that existing hydrogels were difficult to have multiple properties at the same time, and achieved efficient antibacterial, visual observation and good tensile properties.
Patent Information
- Application Number
- CN202411951346.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing medical hydrogels are difficult to have both biocompatible, tissue adhesion, wound visibility, antibacterial and stretchability, and cannot meet the treatment needs of wounds at the moving joints or heads.
A highly transparent adhesion nanocellulose-based antibacterial hydrogel was developed. By assembling components such as nanocellulose, guanidine-based antibacterial agent, hydroxy polymer and macromolecular hydrophilic colloid under physical-chemical cross-linking, a hydrogel with excellent antibacterial properties, transmittance and tensile properties were formed.
The hydrogel has an antibacterial rate of Staphylococcus aureus and E. coli, and has a transmittance of about 85%. It is biocompatible and stretchable. It is suitable for antibacterial medical dressings at the sports joints, providing visual treatment and reducing secondary damage during wound dressing.
Smart Images

Figure CN119798714A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical materials, and particularly relates to a highly transparent and adhesive nanocellulose-based antibacterial hydrogel and a preparation method and application thereof. Background Art
[0002] Human surface trauma is generally caused by bumps, surgery, burns, scalds and chronic diseases. As an important barrier of the human body, the skin is inevitably exposed to the outside air after injury, which increases the risk of infection on the wound surface and prolongs the wound healing time. The wound healing process mainly includes hemostasis, inflammation, proliferation and remodeling. At present, common wound dressings mainly include gauze, bandages, cotton flannel cloth, etc., because they cannot directly observe the actual healing state of the wound and are prone to secondary damage when replaced. In response to current problems, researchers have begun to develop new medical dressings, such as electrospinning fiber membrane type, foam sponge type, hydrogel type, etc. Among them, hydrogel medical dressings are widely used in wound care such as skin knife wounds, burns, scalds and surgical clinics because of their high water content, high moisture retention, softness and good elasticity. However, it is impossible to visualize the wound during use, and auxiliary materials are required to fix it to complete the healing of the wound. The ideal wound dressing needs to have many aspects of performance, not only including the advantages of the material itself, but also good biocompatibility, antibacterial, adhesion, transparency, stretchability and other properties to promote collagen growth and promote blood vessel growth. Therefore, there is an urgent need to prepare a medical dressing with high transparency, adhesion and antibacterial properties to make up for the current shortcomings.
[0003] The currently disclosed medical hydrogels cannot simultaneously possess the properties of biocompatibility, tissue adhesion, wound visibility, antibacterial properties, stretchability, etc., to meet the treatment of special parts (sports joints or head wounds). For example, the invention with the publication number CN113679881A discloses a medical dressing with antibacterial properties and a preparation method thereof, in order to improve the antibacterial properties of the lignin / chitosan / PVA hydrogel medical dressing in the prior art, and to add antibacterial metal nanoparticles into the hydrogel medical dressing; the invention with the authorization number CN109821060B discloses a preparation method of a hydrogel medical dressing for promoting wound healing, the preparation method is to first prepare a reddish-brown CuS@MoS composite structure by a hydrothermal method, and then uniformly dope it into a polyvinyl alcohol solution, and after several freeze-thaw cycles, form a CuS@MoS hydrogel to prepare a wound healing dressing. The above medical dressings all ignore their biocompatibility with wounds. The invention with the publication number CN118649283A discloses an antibacterial hydrogel-based wound dressing with excellent biocompatibility and a preparation method thereof. By constructing a k-carrageenan network of a physical-chemical double cross-linking system and adding a functional factor Me1-Zn, a double cross-linked carrageenan hydrogel antibacterial dressing is prepared. The obtained multifunctional antibacterial wound dressing has excellent antibacterial properties, mechanical properties, and biocompatibility, can promote wound healing, and shows potential for wound healing applications, but its tensile strain is small, the tensile strain is less than 2.0%, and the tensile stress is greater than 200kPa, indicating that the tensile film-forming property is poor and cannot adapt to wound healing at the motion joint. Among them, the invention with the authorization number CN11490405B discloses a hydrogel medical dressing containing a Chinese medicine extract and a preparation method thereof. The elongation at break of the obtained hydrogel is 80%. Although its elongation at break is relatively increased, its adhesion to skin tissue is not mentioned. The invention with the publication number CN116473913A discloses a method for preparing an injectable adhesive hydrogel loaded with Chinese medicine nanoparticles and its application. The prepared hydrogel has good adhesion, but its transmittance under visible light conditions, stretchability, biocompatibility, antibacterial properties, etc. have not been studied. Therefore, it is very important to study an antibacterial medical dressing that simultaneously meets the requirements of biocompatibility, tissue adhesion, visibility, antibacterial and stretchability for wounds. Summary of the invention
[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a highly transparent and adhesive nanocellulose-based antibacterial hydrogel and its preparation and application. The antibacterial hydrogel developed by the present invention has an antibacterial rate of more than 99% against Staphylococcus aureus and Escherichia coli, and a transmittance of about 85% in the visible light wave range. It not only meets the requirements of visual observation of wound healing, but also has the characteristics of biocompatibility and stretchability. It becomes an ideal antibacterial medical dressing carrier for sports joints, provides patients with visual treatment of wounds and avoids secondary damage caused by wound dressing changes. It is one of the potential materials for drug-carrying functional dressings in the future.
[0005] The present invention provides a nanocellulose-based hydrogel, wherein the hydrogel components include, by mass percentage:
[0006]
[0007] Preferably, the guanidine antibiotic is a biguanidine or monoguanidine antibiotic; wherein the biguanide antibiotics include one or more of chlorhexidine, polyhexamethylene biguanide hydrochloride, polyhexamethylene biguanide, and polyaminopropyl biguanide; the monoguanide antibiotics include one or more of polyhexamethylene guanidine hydrochloride, polyhexamethylene guanidine stearate, polyhexamethylene guanidine propionate, and polyhexamethylene guanidine phosphate.
[0008] Furthermore, the guanidine-based antibacterial agent is a biguanide-based antibacterial agent.
[0009] Furthermore, the biguanide-based antibacterial agent is polyhexamethylene biguanide hydrochloride.
[0010] Preferably, the nanocellulose includes one or more of nanocellulose crystals and nanocellulose fibers.
[0011] Furthermore, the nanocellulose is prepared from at least one of cotton, hemp, bamboo, trees and crops as raw materials by using an acid method, a TEMPO oxidation method or a mechanical method.
[0012] Furthermore, the nanocellulose is extracted from cotton fabric.
[0013] Preferably, the hydroxy polymer includes one or more of polyvinyl alcohol and polyethylene glycol; the macromolecular hydrophilic colloid includes but is not limited to gelatin.
[0014] The molecular weight of the macromolecular hydrophilic colloid is 50,000 to 200,000 Da.
[0015] Furthermore, the hydroxy polymer is medical grade polyvinyl alcohol.
[0016] Furthermore, the macromolecular hydrophilic colloid is gelatin formed by partial degradation of collagen in connective tissue of animals (such as cows, etc.).
[0017] Preferably, the cross-linking agent is one or more compounds containing borate ions.
[0018] Furthermore, the compound containing borate ions includes sodium tetraborate decahydrate; wherein the concentration of the sodium tetraborate decahydrate solution is 0.05M to 0.20M.
[0019] Furthermore, the nanocellulose extracted from cotton plants is nanocellulose fibers. A large number of free hydroxyl groups in the nanocellulose form strong hydrogen bonds with polyvinyl alcohol between the nanocellulose fibers and the guanidine-based antibacterial agent, and chemically cross-link with sodium tetraborate decahydrate to form reversible ester bonds. Combined with the biocompatibility, adhesion and film-forming properties of gelatin, a series of physical-chemical cross-linkings are performed to produce highly transparent and adhesive nanocellulose-based antibacterial hydrogels, which are suitable for medical dressings for various wounds.
[0020] The present invention provides a method for preparing any of the nanocellulose-based hydrogels, comprising:
[0021] (1) mixing an aqueous solution of nanocellulose and a guanidine-based antimicrobial agent to obtain a first solution;
[0022] (2) mixing the hydroxy polymer and the first solution of step (1), stirring, and obtaining a second solution;
[0023] (3) mixing the macromolecular hydrophilic colloid and the second solution of step (2), stirring to obtain a third solution;
[0024] (4) mixing the cross-linking agent and the third solution of step (3), cross-linking, and centrifuging to obtain a nanocellulose-based hydrogel.
[0025] In step (1), nanocellulose is dispersed in an aqueous solution of a guanidine-based antimicrobial agent to obtain a first solution.
[0026] In the step (1), the dispersion temperature is 22° C. to 27° C., the magnetic stirring time is 15 min to 45 min, and the stirring speed is 300 r / min to 800 r / min.
[0027] The nanocellulose in step (1) is natural nanocellulose fiber prepared by a mechanical method using cotton-containing plants as raw materials.
[0028] The mechanical method is to grind the absorbent cotton with a ball mill. Before grinding with the ball mill, the absorbent cotton is sheared with a clean crusher, and after the cotton is finely ground, it is put into the ball mill, first grind for 10-30 minutes, stop for 2-5 minutes, grind for 30-40 minutes, stop for 2-5 minutes, grind for 45-60 minutes, grind and stop in sequence, and ensure that the size of the absorbent cotton is between microns. Then a high-pressure homogenizer is used for 10 to 20 cycles, and the air inlet pressure gauge is below 0.7MPa during homogenization, and the maximum pressure value is below 100MPa.
[0029] The shearing time is 10-30 min.
[0030] In step (2), the hydroxy polymer is added to the first solution of step (1).
[0031] The stirring in step (2) is performed at 80° C.-95° C. for 90-210 min.
[0032] Furthermore, in step (2), the stirring rate is 300 r / min-800 r / min.
[0033] In step (3), the macromolecular hydrophilic colloid is added to the second solution of step (2).
[0034] In the step (3), the stirring temperature is 50°C-75°C and the stirring time is 60min-120min.
[0035] Furthermore, in step (3), the stirring rate is 200 r / min-500 r / min.
[0036] The cross-linking in step (4) is at 35°C to 45°C; the centrifugation speed is 3000r / min-6000r / min, and the centrifugation time is 10min to 40min.
[0037] In step (4), the third solution of step (3) is cooled to 35° C. to 45° C. and then mixed with a cross-linking agent to undergo cross-linking.
[0038] The present invention provides a use of any of the nanocellulose-based hydrogels in a medical dressing.
[0039] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel prepared by the method of the present invention has an antibacterial rate of more than 99% against Staphylococcus aureus and Escherichia coli, a transmittance of about 85%, and has the characteristics of biocompatibility, adhesion and stretchability, and can be used as a medical dressing.
[0040] The invention provides an antibacterial hydrogel, wherein the antibacterial hydrogel uses the nanofiber-based hydrogel as a carrier to load antibacterial drugs.
[0041] The present invention provides an application of the nanofiber-based antibacterial hydrogel in medical dressings, such as medical dressings for sports joints.
[0042] The present invention mainly provides a nanocellulose-based antibacterial hydrogel with excellent antibacterial properties, high transmittance, tensile properties, tissue adhesion and biocompatibility, etc., which is formed by using nanocellulose fibers as building units to form an interconnected nanocellulose porous network structure, so that it forms a dense hydrogen bond network with antibacterial agents, hydroxyl polymers and macromolecular hydrophilic colloids, giving it a highly transparent and adhesive nanocellulose-based antibacterial hydrogel with excellent antibacterial properties, high transmittance, and tensile properties, tissue adhesion and biocompatibility.
[0043] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel of the present invention uses natural cotton plants as raw materials, and adopts a mechanical method to extract biocompatible, biodegradable and low-cost nanocellulose fibers and guanidine-based antibacterial agents and macromolecular hydrophilic colloids to form hydrogen bonds and tightly combine with hydroxyl polymers (such as polyvinyl alcohol) polyvinyl alcohol and reversible ester bonds formed by a cross-linking agent sodium tetraborate decahydrate solution, and then forms a highly transparent and adhesive nanocellulose-based antibacterial hydrogel through physical and chemical cross-linking.
[0044] The preparation method of the present invention first disperses nanocellulose fibers in a guanidine-based antibacterial agent solution at room temperature to prepare a nanocellulose fiber / guanidine-based antibacterial agent suspension, raises the temperature to fully dissolve the hydroxyl polymer, then lowers the temperature to dissolve the macromolecular hydrophilic colloid, and when the temperature drops to about 37°C, performs physical and chemical crosslinking with a crosslinking agent sodium tetraborate decahydrate solution to prepare a highly transparent and adhesive nanocellulose-based antibacterial hydrogel, which not only has high transparency, antibacterial performance, tensile performance, and biocompatibility, but also has stable tissue adhesion at motion joints, effectively preventing the medical dressing from slipping during use, and is suitable for the field of new medical antibacterial dressings.
[0045] The significant advantage of the present invention is that the nanocellulose fibers extracted from natural cotton plants can be effectively fixed together with guanidine-based antibacterial agents by covalent bonds or physical adsorption, thereby giving the nanocellulose fibers antibacterial properties. The selected guanidine-based antibacterial agents have good killing effects on bacterial propagules, fungi and some viruses, and can be used for daily cleaning of fruits and vegetables. Moreover, they are very soluble in water and form hydrogen bonds with a large number of free hydroxyl groups in the nanocellulose fibers in the nanocellulose fibers and guanidine-based antibacterial agent solutions. The preparation method of first heating and then cooling is adopted to fully dissolve the hydroxyl polymer and the macromolecular hydrophilic colloid, and then chemically cross-link with a cross-linking agent sodium tetraborate decahydrate solution at about 37°C to form a reversible ester bond to prepare a highly transparent and adhesive nanofiber-based antibacterial hydrogel.
[0046] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel prepared by the present invention has a transmittance of about 85% at visible light wavelengths, and an antibacterial rate of more than 99% against Staphylococcus aureus and Escherichia coli. It not only has good biocompatibility, adhesion and stretchability, but also has the characteristics of high transparency and antibacterial rate, making it an ideal new type of medical antibacterial dressing carrier.
[0047] Preferably, the present invention uses natural cotton plants as raw materials, mechanically extracts nanocellulose fibers, and fixes them with guanidine-based antibacterial agent solutions through covalent bonds or physical adsorption. The release of guanidine-based antibacterial agents is controlled by nanocellulose fibers to prolong the antibacterial effect. The nanocellulose fibers loaded with guanidine-based antibacterial agents form dense hydrogen bonds with hydroxyl polymers and macromolecular hydrophilic colloids, and strengthen the formation of strong reversible ester bonds with sodium tetraborate decahydrate solution. The highly transparent and adhesive nanocellulose-based antibacterial hydrogel is centrifugally defoamed. The controllable preparation technology of the pore structure of the highly transparent and adhesive nanocellulose-based antibacterial hydrogel is broken through, which is conducive to controlling the release of guanidine-based antibacterial agents, realizing the preparation of three-dimensional network highly transparent and adhesive nanocellulose-based antibacterial hydrogel dressings, and becoming a highly potential antibacterial medical drug-carrying material.
[0048] Beneficial Effects
[0049] (1) The cotton plant nanocellulose fibers provided by the present invention can effectively absorb guanidine-based antimicrobial agents, so that they can serve as a bridge structure in the hydrogel to construct a three-dimensional network structure, fill the interior, play a defoaming function, enhance the antibacterial property, tissue adhesion and self-healing property of the hydrogel, and become an ideal medical dressing base material, effectively preventing the medical dressing from slipping when used on sports joints;
[0050] (2) The highly transparent and adhesive nanocellulose-based antibacterial hydrogel provided by the present invention has a transmittance of about 85% under visible light wavelength, and the diameters of the antibacterial zones against Staphylococcus aureus and Escherichia coli are 1.50cm-2.58cm and 1.05cm-1.79cm, respectively, and the antibacterial rates are both greater than 99%. This indicates that the prepared highly transparent and adhesive nanocellulose-based antibacterial hydrogel has visualization and antibacterial effects when treating wounds, promoting wound healing, and is an ideal new type of medical antibacterial dressing carrier;
[0051] (3) The method for preparing highly transparent and adhesive nanocellulose-based antibacterial hydrogel provided by the present invention is simple. The antibacterial agent is effectively combined with the nanocellulose fiber by covalent bonds or physical adsorption under room temperature conditions, and the hydroxyl polymer and the macromolecular hydrophilic colloid are fully dissolved by first heating and then cooling, and then physically and chemically cross-linked with sodium tetraborate decahydrate solution, thereby reducing the preparation cost and realizing large-scale mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 These are stress-strain curves of hydrogels prepared from nanocellulose using three different methods;
[0053] Figure 2 This is a photo of a highly transparent and adhesive nanocellulose antibacterial hydrogel film prepared in Example 3;
[0054] Figure 3 is the transmittance of the hydrogels prepared in the implementation examples and the comparative examples at visible light wavelengths;
[0055] Figure 4 It is a physical picture of the transparency of the hydrogel prepared in the implementation example and the comparative example;
[0056] Figure 5 This is a physical picture of the healing stretching of Example 3;
[0057] Figure 6 is a stress-strain curve diagram of the hydrogel prepared in the implementation example and the comparative example;
[0058] Figure 7 This is a physical picture of various shape transformations of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel prepared in Example 3;
[0059] Figure 8 It is the healing time diagram of the implementation case and the comparative example and the actual image of the test sample of case 3;
[0060] Fig. 9 This is a photograph of the adhesion effect of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel prepared in Example 3 on skin joint tissues and different materials;
[0061] Fig.10 The cross-sectional and longitudinal SEM images (500× and 1000×) of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel prepared in Example 3;
[0062] Fig.11 This is a microscopic image of the inhibition zone of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel against Staphylococcus aureus and Escherichia coli prepared in the implementation case; DETAILED DESCRIPTION
[0063] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0064] The cotton plant raw material used in the examples was provided by Joy Home Textile Co., Ltd.; the guanidine antibacterial agent, hydroxyl polymer and sodium tetraborate decahydrate were purchased from Aladdin Reagent (Shanghai) Co., Ltd.; the copper ion antibacterial agent was provided by Shandong Yellow River Delta Textile Science and Technology Research Institute Co., Ltd.; the macromolecular hydrophilic colloid, gelatin, had a molecular weight of 100,000 Da.
[0065] The high-pressure homogenizer used in the embodiment is from Suzhou Aisen Pharmaceutical Equipment Co., Ltd., model HPH-L2; the multifunctional crusher is from Jiangxi Ganyun Food Machinery Co., Ltd., model GY-FS-08; the planetary ball mill is from Beijing Gridman Instrument Equipment Co., Ltd., model BM6pro; the constant temperature magnetic stirrer is from Shanghai Heqi Instrument Co., Ltd., model Feb-85; the digital display DC constant speed stirrer is from Jiangsu Jinyi Technology Co., Ltd., model JJ-6; the electric inspection screening machine is from Zibo Hengsen Construction Installation Engineering Co., Ltd., model HS6277200; the centrifuge is from Changsha Yingtai Instrument Co., Ltd., model TGL16; the electronic balance is from Shanghai Sunny Hengping Scientific Instrument Co., Ltd., model FA2004.
[0066] First, the embodiment of the present invention extracts nanocellulose fibers from cotton plants, and the specific process is as follows:
[0067] First, clean absorbent cotton is selected for grinding. Before using the ball mill for grinding, the absorbent cotton is repeatedly sheared with a clean multifunctional pulverizer, and then the cotton is put into the ball mill after being finely ground. It is first ground for 10 minutes, stopped for 2 minutes, then ground for 30 minutes, stopped for 2 minutes, and then ground for 45 minutes, and then ground-stopped in sequence to ensure that the size of the absorbent cotton is between microns. Then a high-pressure homogenizer is used for 10 to 20 cycles. During homogenization, the air inlet pressure gauge is below 0.7MPa, and the maximum pressure value is below 100MPa to obtain nanocellulose fibers.
[0068] Example 1
[0069] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following components by mass percentage: 75.9992% deionized water, 0.0008% polyhexamethylene biguanide hydrochloride, 1.0% nanocellulose fiber, 5% polyvinyl alcohol, 6% gelatin, and 12% 0.1M sodium tetraborate decahydrate.
[0070] The preparation method of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following steps:
[0071] (1) dissolving polyhexamethylene biguanide hydrochloride in deionized water and dissolving it at room temperature to prepare a guanidine-based antibacterial agent solution with a mass fraction of 0.0008%;
[0072] (2) the nanocellulose fibers extracted from cotton plants are uniformly dispersed in the guanidine-based antimicrobial agent solution of step (1) under magnetic stirring conditions to prepare a nanocellulose fiber / guanidine-based antimicrobial agent suspension with a mass fraction of 1.0%;
[0073] (3) adding medical polyvinyl alcohol to the nanocellulose fiber / guanidine antibacterial agent suspension obtained in step (2) to prepare a nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol mixed solution with a mass fraction of 5%, raising the temperature to 90° C., stirring at 90° C. for 180 min until fully dissolved, with a stirring speed of 500 r / min;
[0074] (4) cooling the solution obtained in step (3) to 70° C. while stirring, adding gelatin to prepare a mixed solution of nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol / gelatin with a mass fraction of 6%, stirring at 70° C. for 60 min at a stirring speed of 500 r / min;
[0075] (5) cooling the solution obtained in step (4) to 37° C. while stirring;
[0076] (6) slowly dripping the prepared 0.1 M sodium tetraborate decahydrate solution into the solution obtained in step (5), and synthesizing a highly transparent and adhesive nanocellulose-based antibacterial hydrogel through physical-chemical crosslinking under the action of polytetrafluoroethylene double blade stirring;
[0077] (7) The highly transparent and adhesive nanocellulose-based antibacterial hydrogel obtained in step (6) is centrifuged at a speed of 5000 r / min for 20 min to fully cross-link it, thereby preparing a new type of medical dressing with high transparency, adhesion, antibacterial, high tensile strength and self-healing properties.
[0078] Example 2
[0079] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following components by mass percentage: 75.996% deionized water, 0.004% polyhexamethylene biguanide hydrochloride, 1.0% nanocellulose fiber, 5% polyvinyl alcohol, 6% gelatin, and 12% 0.1M sodium tetraborate decahydrate.
[0080] The preparation method of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following steps:
[0081] (1) dissolving polyhexamethylene biguanide hydrochloride in deionized water and dissolving it at room temperature to prepare a guanidine-based antibacterial agent solution with a mass fraction of 0.004%;
[0082] (2) the nanocellulose fibers extracted from cotton plants are uniformly dispersed in the guanidine-based antimicrobial agent solution of step (1) under magnetic stirring conditions to prepare a nanocellulose fiber / guanidine-based antimicrobial agent suspension with a mass fraction of 1.0%;
[0083] (3) adding medical polyvinyl alcohol to the nanocellulose fiber / guanidine antibacterial agent suspension obtained in step (2) to prepare a nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol mixed solution with a mass fraction of 5%, raising the temperature to 90° C., stirring at 90° C. for 180 min until fully dissolved, with a stirring speed of 500 r / min;
[0084] (4) cooling the solution obtained in step (3) to 70° C. while stirring, adding gelatin to prepare a mixed solution of nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol / gelatin with a mass fraction of 6%, stirring at 70° C. for 60 min at a stirring speed of 500 r / min;
[0085] (5) cooling the solution obtained in step (4) to 37° C. while stirring;
[0086] (6) slowly dripping the prepared 0.1 M sodium tetraborate decahydrate solution into the solution obtained in step (5), and synthesizing a highly transparent and adhesive nanocellulose-based antibacterial hydrogel through physical-chemical crosslinking under the action of polytetrafluoroethylene double blade stirring;
[0087] (7) The highly transparent and adhesive nanocellulose-based antibacterial hydrogel obtained in step (6) is centrifuged at a speed of 5000 r / min for 20 min to fully cross-link it, thereby preparing a new type of medical dressing with high transparency, adhesion, antibacterial, high tensile strength and self-healing properties.
[0088] Example 3
[0089] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following components by mass percentage: 75.98% deionized water, 0.02% polyhexamethylene biguanide hydrochloride, 1.0% nanocellulose fiber, 5% polyvinyl alcohol, 6% gelatin, and 12% 0.1M sodium tetraborate decahydrate.
[0090] The preparation method of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following steps:
[0091] (1) dissolving polyhexamethylene biguanide hydrochloride in deionized water and dissolving it at room temperature to prepare a guanidine-based antibacterial agent solution with a mass fraction of 0.02%;
[0092] (2) the nanocellulose fibers extracted from cotton plants are uniformly dispersed in the guanidine-based antimicrobial agent solution of step (1) under magnetic stirring conditions to prepare a nanocellulose fiber / guanidine-based antimicrobial agent suspension with a mass fraction of 1.0%;
[0093] (3) adding medical polyvinyl alcohol to the nanocellulose fiber / guanidine antibacterial agent suspension obtained in step (2) to prepare a nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol mixed solution with a mass fraction of 5%, raising the temperature to 90° C., stirring at 90° C. for 180 min until fully dissolved, with a stirring speed of 500 r / min;
[0094] (4) cooling the solution obtained in step (3) to 70° C. while stirring, adding gelatin to prepare a mixed solution of nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol / gelatin with a mass fraction of 6%, stirring at 70° C. for 60 min at a stirring speed of 500 r / min;
[0095] (5) cooling the solution obtained in step (4) to 37° C. while stirring;
[0096] (6) slowly dripping the prepared 0.1 M sodium tetraborate decahydrate solution into the solution obtained in step (5), and synthesizing a highly transparent and adhesive nanocellulose-based antibacterial hydrogel through physical-chemical crosslinking under the action of polytetrafluoroethylene double blade stirring;
[0097] (7) The highly transparent and adhesive nanocellulose-based antibacterial hydrogel obtained in step (6) is centrifuged at a speed of 5000 r / min for 20 min to fully cross-link it, thereby preparing a new type of medical dressing with high transparency, adhesion, antibacterial, high tensile strength and self-healing properties.
[0098] Example 4
[0099] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following components by mass percentage: 75.9% deionized water, 0.1% polyhexamethylene biguanide hydrochloride, 1.0% nanocellulose fiber, 5% polyvinyl alcohol, 6% gelatin, and 12% 0.1M sodium tetraborate decahydrate.
[0100] The preparation method of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following steps:
[0101] (1) dissolving polyhexamethylene biguanide hydrochloride in deionized water and dissolving it at room temperature to prepare a guanidine-based antibacterial agent solution with a mass fraction of 0.1%;
[0102] (2) the nanocellulose fibers extracted from cotton plants are uniformly dispersed in the guanidine-based antimicrobial agent solution of step (1) under magnetic stirring conditions to prepare a nanocellulose fiber / guanidine-based antimicrobial agent suspension with a mass fraction of 1.0%;
[0103] (3) adding medical polyvinyl alcohol to the nanocellulose fiber / guanidine antibacterial agent suspension obtained in step (2) to prepare a nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol mixed solution with a mass fraction of 5%, raising the temperature to 90° C., stirring at 90° C. for 180 min until fully dissolved, with a stirring speed of 500 r / min;
[0104] (4) cooling the solution obtained in step (3) to 70° C. while stirring, adding gelatin to prepare a mixed solution of nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol / gelatin with a mass fraction of 6%, stirring at 70° C. for 60 min at a stirring speed of 500 r / min;
[0105] (5) cooling the solution obtained in step (4) to 37° C. while stirring;
[0106] (6) slowly dripping the prepared 0.1 M sodium tetraborate decahydrate solution into the solution obtained in step (5), and synthesizing a highly transparent and adhesive nanocellulose-based antibacterial hydrogel through physical-chemical crosslinking under the action of polytetrafluoroethylene double blade stirring;
[0107] (7) The highly transparent and adhesive nanocellulose-based antibacterial hydrogel obtained in step (6) is centrifuged at a speed of 5000 r / min for 20 min to fully cross-link it, thereby preparing a new type of medical dressing with high transparency, adhesion, antibacterial, high tensile strength and self-healing properties.
[0108] Comparative Example 1
[0109] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following components by mass percentage: 75.5% deionized water, 0.5% polyhexamethylene biguanide hydrochloride, 1.0% nanocellulose fiber, 5% polyvinyl alcohol, 6% gelatin, and 12% 0.1M sodium tetraborate decahydrate.
[0110] A method for preparing a highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following steps:
[0111] (1) dissolving polyhexamethylene biguanide hydrochloride in deionized water and dissolving it at room temperature to prepare a guanidine-based antibacterial agent solution with a mass fraction of 0.5%;
[0112] (2) the nanocellulose fibers extracted from cotton plants are uniformly dispersed in the guanidine-based antimicrobial agent solution of step (1) under magnetic stirring conditions to prepare a nanocellulose fiber / guanidine-based antimicrobial agent suspension with a mass fraction of 1.0%;
[0113] (3) adding medical polyvinyl alcohol to the nanocellulose fiber / guanidine antibacterial agent suspension obtained in step (2) to prepare a nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol mixed solution with a mass fraction of 5%, raising the temperature to 90° C., stirring at 90° C. for 180 min until fully dissolved, with a stirring speed of 500 r / min;
[0114] (4) cooling the solution obtained in step (3) to 70° C. while stirring, adding gelatin to prepare a mixed solution of nanocellulose fiber / guanidine antibacterial agent / polyvinyl alcohol / gelatin with a mass fraction of 6%, stirring at 70° C. for 60 min at a stirring speed of 500 r / min;
[0115] (5) cooling the solution obtained in step (4) to 37° C. while stirring;
[0116] (6) slowly dripping the prepared 0.1 M sodium tetraborate decahydrate solution into the solution obtained in step (5), and synthesizing a highly transparent and adhesive nanocellulose-based antibacterial hydrogel through physical-chemical crosslinking under the action of polytetrafluoroethylene double blade stirring;
[0117] (7) The highly transparent and adhesive nanocellulose-based antibacterial hydrogel obtained in step (6) is centrifuged at a speed of 5000 r / min for 20 min to fully cross-link it, thereby preparing a new type of medical dressing with high transparency, adhesion, antibacterial, high tensile strength and self-healing properties.
[0118] Comparative Example 2
[0119] The highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following components by mass percentage: 75.98% deionized water, 0.02% copper ion antibacterial agent, 1.0% nanocellulose fiber, 5% polyvinyl alcohol, 6% gelatin, and 12% 0.1M sodium tetraborate decahydrate.
[0120] The preparation method of a highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing comprises the following steps:
[0121] (1) dropping a copper ion antibacterial agent solution into a nanocellulose solution having a mass fraction of 1.0% to prepare a nanocellulose / copper ion antibacterial agent suspension having a mass fraction of 0.02%;
[0122] (2) adding medical polyvinyl alcohol to the nanocellulose / copper ion antibacterial agent suspension obtained in step (1) to prepare a nanocellulose fiber / copper ion antibacterial agent / polyvinyl alcohol mixed solution with a mass fraction of 5%, raising the temperature to 90° C., stirring at 90° C. for 180 min until fully dissolved, with a stirring speed of 500 r / min;
[0123] (4) cooling the solution obtained in step (3) to 70° C. while stirring, adding gelatin to prepare a mixed solution of nanocellulose fiber / copper ion / polyvinyl alcohol / gelatin with a mass fraction of 6%, stirring at 70° C. for 60 min at a stirring speed of 500 r / min;
[0124] (5) cooling the solution obtained in step (4) to 37° C. while stirring;
[0125] (6) slowly dripping the prepared 0.1 M sodium tetraborate decahydrate solution into the solution obtained in step (5), and synthesizing a highly transparent and adhesive nanocellulose-based antibacterial hydrogel through physical-chemical crosslinking under the action of polytetrafluoroethylene double blade stirring;
[0126] (7) The highly transparent and adhesive nanocellulose-based antibacterial hydrogel obtained in step (6) is centrifuged at a speed of 5000 r / min for 20 min to fully cross-link it, thereby preparing a new type of medical dressing with high transparency, adhesion, antibacterial, high tensile strength and self-healing properties.
[0127] Analysis of attached pictures
[0128] Mechanical properties of hydrogels prepared by three different methods:
[0129] Figure 1 SNCH, TNCH and MNCH are nanocellulose extracted from cotton fibers by sulfuric acid method, TEMPO oxidation method and mechanical method respectively, and are prepared into a highly transparent and adhesive nanocellulose-based hydrogel. From the stress-strain curve, it can be seen that the elongation of the nanocellulose hydrogel extracted by the mechanical method is greater than 1000%, and the elongation of the nanocellulose hydrogel extracted by the other two methods is close, at about 650%. In addition, the hydrogel prepared by the mechanical method has the lowest strength, which is more conducive to the hydrogel changing according to the movement of the joints during use.
[0130] Transparency test of the prepared highly transparent adhesive nanocellulose-based antibacterial hydrogel medical dressing:
[0131] like Figure 2 As shown in Figure 2, it can be found that the highly transparent and adhesive nanocellulose-based antibacterial hydrogel has good film-forming properties and Figure 3 It can be found that the transmittance of the embodiment under visible light wavelength is high, and its transmittance value is about 85%; the transmittance value of comparative example 1 is lower than 80%, and the transmittance value of comparative example 2 under visible light is unstable and fluctuates up and down. Figure 4 When attached to a pattern marked with the DHU logo, it can be found that the embodiment is clearly visible under the highly transparent adhesive nanocellulose-based antibacterial hydrogel medical dressing, further illustrating the visual application of the highly transparent adhesive nanocellulose-based antibacterial hydrogel medical dressing.
[0132] Healing tensile test of the prepared highly transparent adhesive nanocellulose-based antibacterial hydrogel medical dressing:
[0133] like Figure 5 , take part of the highly transparent and adhesive nanocellulose-based antibacterial hydrogel and cut it into two with a blade, then let it stand for 20 seconds without external force, and then stretch it. It can be found that the highly transparent and adhesive nanocellulose-based antibacterial hydrogel has healed at the point where it is divided into two, and there is no breakage under non-uniform tension; Figure 6 As shown, it is a stress-strain curve diagram of the embodiment and the comparative example, wherein the elongation of the embodiment 3 is the best, about 1400%, while that of the comparative examples 1-2 is about 200%. And take part of the highly transparent and adhesive nanocellulose-based antibacterial hydrogel, stretch it and then form a ball to make a butterfly pattern, and then the butterfly pattern is self-healed into a ball, which can be repeated for a long time. Figure 7 As shown, it further indicates that the highly transparent adhesive nanocellulose-based antibacterial hydrogel has good healing and stretchability. The actual picture of healing time and stretching is shown in Figure 8 shown.
[0134] Test of the joint tissue adhesion of the prepared highly transparent adhesive nanocellulose-based antibacterial hydrogel medical dressing:
[0135] like Fig. 9 As shown, the highly transparent adhesion nanocellulose-based antibacterial hydrogel medical dressing was attached to the finger joints, bent at different angles, and then repositioned, and it was found that the highly transparent adhesion nanocellulose-based antibacterial hydrogel medical dressing was still attached to the finger joints, without slipping or fluctuations that affected the conformity of the highly transparent adhesion nanocellulose-based antibacterial hydrogel medical dressing to the tissue joints. In addition, it can be found that the highly transparent adhesion nanocellulose-based antibacterial hydrogel medical dressing also has a certain adhesion to plastic, iron, polytetrafluoroethylene, rubber and glass, indicating that the highly transparent adhesion nanocellulose-based antibacterial hydrogel medical dressing not only has good toughness, but also has good adhesion, and can stay on human skin for 5h-8h to meet the needs of new medical dressings.
[0136] Microscopic morphology observation of the prepared highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing;
[0137] like Fig.10 As shown, the cross-sectional and longitudinal cross-sectional views of Example 3 of the highly transparent and adhesive nanocellulose-based antibacterial hydrogel, the pore channels are bridged by the pore walls, presenting a relatively tight three-dimensional network structure, the pore structure is interconnected, the pore structure is stable, and the drug loading can be effectively carried out, alleviating the drug "burst release" phenomenon that may occur during the drug release process.
[0138] Analysis of the antibacterial effect of the prepared highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing;
[0139] like Fig.11 The implementation cases and comparative examples were used to conduct antibacterial zone tests on Staphylococcus aureus and Escherichia coli, and it was found that the highly transparent and adhesive nanocellulose-based antibacterial hydrogel had antibacterial diffusion properties on both Staphylococcus aureus and Escherichia coli. The diameter of the antibacterial zone for Staphylococcus aureus was 1.50cm-2.58cm, and the diameter of the antibacterial zone for Escherichia coli was 1.05cm-1.79cm, indicating that the prepared highly transparent and adhesive nanocellulose-based antibacterial hydrogel medical dressing can be used as a base material for antibacterial drug-loaded medical dressings.
Claims
1. A nanocellulose-based hydrogel, characterized in that By mass percentage, the hydrogel components include:
2. The nanocellulose-based hydrogel according to claim 1, characterized in that The guanidine-based antibacterial agent is a biguanidine-based or monoguanidine-based antibacterial agent; wherein the biguanidine-based antibacterial agent includes one or more of chlorhexidine, polyhexamethylene biguanide hydrochloride, polyhexamethylene biguanide, and polyaminopropyl biguanide; the monoguanidine-based antibacterial agent includes one or more of polyhexamethylene guanidine hydrochloride, polyhexamethylene guanidine stearate, polyhexamethylene guanidine propionate, and polyhexamethylene guanidine phosphate.
3. The nanocellulose-based hydrogel according to claim 1, characterized in that The nanocellulose includes one or more of nanocellulose crystals and nanocellulose fibers.
4. The nanocellulose-based hydrogel according to claim 1, characterized in that The hydroxy polymer includes one or more of polyvinyl alcohol and polyethylene glycol; the macromolecular hydrophilic colloid includes gelatin.
5. The nanocellulose-based hydrogel according to claim 1, characterized in that: The cross-linking agent is one or more compounds containing borate ions.
6. The nanocellulose-based hydrogel according to claim 5, characterized in that: The compound containing borate ions includes sodium tetraborate decahydrate.
7. A method for preparing the nanocellulose-based hydrogel according to any one of claims 1 to 6, comprising: (1) mixing an aqueous solution of nanocellulose and a guanidine-based antimicrobial agent to obtain a first solution; (2) mixing the hydroxy polymer and the first solution of step (1), stirring, and obtaining a second solution; (3) mixing the macromolecular hydrophilic colloid and the second solution of step (2), stirring to obtain a third solution; (4) mixing the cross-linking agent and the third solution of step (3), cross-linking, and centrifuging to obtain a nanocellulose-based hydrogel.
8. The preparation method according to claim 7, characterized in that: In step (2), stirring is performed at 80°C-95°C for 90-210 min; and in step (3), stirring is performed at 50°C-75°C for 60 min-120 min.
9. The preparation method according to claim 7, characterized in that: The cross-linking in step (4) is at 35°C to 45°C; the centrifugation speed is 3000r / min to 6000r / min, and the centrifugation time is 10min to 40min.
10. Use of the nanocellulose-based hydrogel according to any one of claims 1 to 6 in medical dressings.
Citation Information
Patent Citations
Antibacterial peptide hydrogel and preparation method thereof
CN115627042A
Hydrogel composition
CN117731825A
Antibacterial wound dressing, method for preparing the same, and use thereof
US20190290676A1
Fiber wound dressing having antibacterial effect and preparation method therefor
WO2012062139A1